2022
DOI: 10.3390/buildings12111944
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Embodied Carbon in Buildings: Background, Approaches and Advancements

Abstract: The environment demands a reduction in greenhouse gas (GHG) emissions, as building and construction are responsible for more than 40% of the energy consumed worldwide and 30% of the world’s GHG emissions. Many countries have aligned themselves with the Paris agreement, following its target of achieving net zero carbon emissions, although some governments are focused on the operational energy efficiency part of the equation instead of the whole equation. This study emphasizes the significance of incorporating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In addition, this study found that, for construction managers, energy efficiency is easier to implement and easier to promote than carbon emission reduction. Likewise, Khan, S.A. [39] et al argue that various types of energy-reduction measures can help to minimize carbon emissions at all levels, while being cheaper to invest in and easier to incentivize government policies to promote.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study found that, for construction managers, energy efficiency is easier to implement and easier to promote than carbon emission reduction. Likewise, Khan, S.A. [39] et al argue that various types of energy-reduction measures can help to minimize carbon emissions at all levels, while being cheaper to invest in and easier to incentivize government policies to promote.…”
Section: Discussionmentioning
confidence: 99%
“…The research delves into often-overlooked considerations regarding end-of-life implications in carbon footprint evaluations [106]. By scrutinizing deconstruction, transportation, reuse/recycling, and disposal phases, this study underscores the significance of responsible waste management practices in curtailing the environmental impact of glamping structures.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Ref. [82] emphasizes the importance of research on embodied carbon emissions in the construction industry and reviews the research background, methods, and progress of embodied carbon. However, the results of this study suggest that although there has been some progress in assessing the embodied carbon of buildings, there are still barriers to reducing carbon emissions.…”
Section: Research Trendsmentioning
confidence: 99%
“…In the field of carbon emissions in the construction industry, uncertainty includes models, parameters, methods, future scenarios, etc. [78,82]. Carbon neutrality can be understood as carbon emissions equal to or less than carbon sink values, sometimes also known as net zero emissions.…”
Section: Research Trendsmentioning
confidence: 99%